2019
DOI: 10.1002/clc.23161
|View full text |Cite
|
Sign up to set email alerts
|

The rationale, design, and methods of a randomized, controlled trial to evaluate the efficacy and safety of an active strategy for the diagnosis and treatment of acute pulmonary embolism during exacerbations of chronic obstructive pulmonary disease

Abstract: Introduction Some previous studies have suggested a high prevalence of pulmonary embolism (PE) during exacerbations of chronic obstructive pulmonary disease (ECOPD). The SLICE trial aims to assess the efficacy and safety of an active strategy for the diagnosis and treatment of PE (vs usual care) in patients hospitalized because of ECOPD. Methods SLICE is a phase III, prospective, international, multicenter, randomized, open‐label, and parallel‐group trial. A total of 74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…21 It remains to be determined in larger studies if, after a negative computed tomographic angiographic scan, a leg compression ultrasound should be systematically added when patients with COPD and acutely worsening respiratory symptoms are admitted. 24 It is an important question because this practice is no longer recommended for patients with suspected pulmonary embolism. 14 Consistent with other studies, mortality was higher among patients with pulmonary embolism than it was for patients without it.…”
Section: Discussionmentioning
confidence: 99%
“…21 It remains to be determined in larger studies if, after a negative computed tomographic angiographic scan, a leg compression ultrasound should be systematically added when patients with COPD and acutely worsening respiratory symptoms are admitted. 24 It is an important question because this practice is no longer recommended for patients with suspected pulmonary embolism. 14 Consistent with other studies, mortality was higher among patients with pulmonary embolism than it was for patients without it.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, patients with AECOPD combined with PE had slightly higher average length of hospitalization (15.7 vs. 14.2 days, P = 0.07) and in‐hospital mortality (6.1% vs. 5.1%, P = 0.62) compared with those of patients without PE 7 . Some previous studies have suggested that PE has a higher prevalence during AECOPD, and it also leads to higher morbidity and mortality in COPD patients 64 . Hassen et al 2 have showed that the risk of ICU hospitalization and mortality in patients with severe COPD increased with the increase in the incidence of PE.…”
Section: Prognosismentioning
confidence: 77%
“… 7 Some previous studies have suggested that PE has a higher prevalence during AECOPD, and it also leads to higher morbidity and mortality in COPD patients. 64 Hassen et al 2 have showed that the risk of ICU hospitalization and mortality in patients with severe COPD increased with the increase in the incidence of PE. Recently, the results of the ELOPE prospective cohort study demonstrated that nearly half of COPD patients with acute PE, most of whom were at low risk, continued to have dyspnea, movement restriction, and other sequelae within 1 year after the disease, which adversely influences the health-related quality of life.…”
Section: Prognosismentioning
confidence: 99%
“…SLICE was a multicenter, open-label, randomized, clinical trial aimed at evaluating whether an active search for PE might improve clinical outcomes in patients with exacerbations of COPD who required hospital admission. The rationale, design and main results of the SLICE study were described previously [ 11 , 12 ]. The trial was conducted in 18 academic hospitals across Spain.…”
Section: Methodsmentioning
confidence: 99%